2017
DOI: 10.1161/strokeaha.116.015915
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Embolic Protection Devices During Transcatheter Aortic Valve Implantation

Abstract: T ranscatheter aortic valve implantation (TAVI) procedures have been associated with silent ischemic cerebral embolism as assessed by diffusion-weighted magnetic resonance imaging (DW-MRI) or high-intensity transient signals as assessed by transcranial Doppler. [1][2][3][4][5][6] Embolic protection devices (EPD) might reduce the risk of cerebral embolic ischemic lesions, either clinically evident cerebrovascular accidents or silent ischemic lesions in patients undergoing TAVI. Nonetheless, the efficacy of EPD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(28 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…With current techniques, successful deployment is achieved over 90% of cases, with success rates ranging from 64%–100%. [8] Materials captured by the filters include thrombus, arterial wall tissue, valve tissue, calcification and foreign material. [9–11] In the Cerebral Protection in Transcatheter Aortic Valve Replacement (SENTINEL) trial, histopathologic debris were found within filters in 99% of patients.…”
Section: Types Of Embolic Protection Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…With current techniques, successful deployment is achieved over 90% of cases, with success rates ranging from 64%–100%. [8] Materials captured by the filters include thrombus, arterial wall tissue, valve tissue, calcification and foreign material. [9–11] In the Cerebral Protection in Transcatheter Aortic Valve Replacement (SENTINEL) trial, histopathologic debris were found within filters in 99% of patients.…”
Section: Types Of Embolic Protection Devicesmentioning
confidence: 99%
“…These devices aim to prevent procedural debris reaching the cerebral vasculature. CEPDs have been shown to be effective in the filtration of debris and decreasing the volume of ischaemic embolic lesions,[8] hence, with the potential for decreasing the risk of clinically evident CVA. In this article, we summarise the available data regarding CEPDs and their clinical significance.…”
mentioning
confidence: 99%
“…The current available evidence in relation to EPD are constituted by a series of observational and 5 randomized studies ( 31 , 58 , 74 76 ), which have been also combined in several meta-analysis ( 77 80 ). Main limitations of randomized trials have been the relatively low number of patients included and using surrogate events such as the number and volume of cerebral lesions as the primary endpoint, instead of clinical neurological events.…”
Section: Embolic Protection Devicesmentioning
confidence: 99%
“…Several meta-analyses have combined the results of the observational and randomized studies. Surrogate end-point such as the number and volume of new brain lesions seemed to be reduced in favor of the EPD ( 77 , 80 ), although differences in the global rate of stroke or death is more controversial. While, some meta-analyses did not show any an statistical differences, other showed a reduction in the combined event of death or stroke using EPD, performing an analysis by the fixed-effects method ( 79 ).…”
Section: Embolic Protection Devicesmentioning
confidence: 99%
“…Indeed, neurological complications due to embolization in transcatheter aortic valve implantation are relatively high 9 ) ; however, its risk factors are yet to be fully elucidated. Furthermore, the use of embolic protection devices still appears to be controversial 10 ) . Thus, the further understanding of possible risk factors and technical advances are also warranted to mitigate the risk of the latest procedure-related complications, including stroke.…”
mentioning
confidence: 99%